The leader mRNA of the histidine attenuator region resembles tRNAHis: possible general regulatory implications. - Ames, B N (1983)
The leader region of the mRNA of the his operon is involved in regulating the frequency of transcription termination through attenuation and therefore expression of the his structural genes. We now report that the his leader mRNA has a remarkable sequence homology with the tRNAHis molecule. Of the 75 nucleotides forming tRNAHis (not counting the -CCA tail), 45 are homologous to nucleotide sequences found in the his leader mRNA. This homology extends to secondary structures which can form in the leader mRNA. The stems and loops of tRNAHis are thus related to those of the his leader mRNA which play a critical role in regulating expression of the his operon through attenuation. Many proteins that bind tRNAHis thus might bind to the similar structures found in the his leader mRNA and influence regulation by favoring the attenuator or anti-attenuator configuration. These include tRNA-modifying enzymes, the histidyl-tRNA synthetase, and the hisG enzyme. The significance of similar structures in other regulatory systems is discussed, particularly in relation to the role of tRNA-modifying enzymes as important regulatory molecules in both prokaryotes and eukaryotes.